Visibility of Japanese Patterns in Mojokerto Public Spaces - Utomo, Kireina Fernanda; Khasanah, Ismatul; Rusmawati, Roosi (Journal of Japanese Language Education and Linguistics, 2025)
This study aims to investigate the prominence of Japanese language usage in public areas of Mojokerto, East Java. This linguistic phenomenon pertains to sociolinguistic settings, rendering it a compelling subject for study. This research employs a descriptive qualitative method to elucidate social phenomena inside the Mojokerto community. Data were collected via observations in Ngoro, Mojosari, and Magersari sub-districts, concentrating on linguistic utilization in education, commerce, and industry. The research was conducted from June 2023 to March 2024 through photographic documentation and interviews with five participants. Two individuals from the trade sector, one from the education sector, and two from the industry sector were present. The collected data consisted of 31 instances of Japanese usage in public settings in Mojokerto, exhibiting diverse patterns. The acquired data is corroborated by interview results indicating that Japanese is extensively utilized in public settings in Mojokerto. The findings of this study indicate that the utilization of Japanese in Mojokerto is grassroots, as there is no governmental involvement.